2020
DOI: 10.1016/j.fsi.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Grass carp reovirus VP56 represses interferon production by degrading phosphorylated IRF7

Abstract: Grass carp reovirus (GCRV) is an efficient pathogen causing high mortality in grass carp, meanwhile, fish interferon (IFN) is a powerful cytokine enabling host cells to establish an antiviral state; therefore, the strategies used by GCRV to escape the cellular IFN response need to be investigated. Here, we report that GCRV VP56 inhibits host IFN production by degrading the transcription factor IFN regulatory factor 7 (IRF7). First, overexpression of VP56 inhibited the IFN production induced by the polyinosinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…IRF3/7 are crucial IFN regulation factors. In a previous report, GCRV VP56 represses IFN production by degrading phosphorylated IRF7 ( 11 ). In the present study, we found that VP56 targets and degrades the immune initial point molecule RIG-I ( Fig.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…IRF3/7 are crucial IFN regulation factors. In a previous report, GCRV VP56 represses IFN production by degrading phosphorylated IRF7 ( 11 ). In the present study, we found that VP56 targets and degrades the immune initial point molecule RIG-I ( Fig.…”
Section: Discussionmentioning
confidence: 82%
“…The functions of VP56 when the virus particle attaches to the host cell and after entry into the cell membrane are still unclear. Although several reports have claimed to understand part of the function of GCRV fiber protein, further research is needed ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For SVCV, the P protein competitively inhibits the kinase activity of TBK1, and the N protein degrades MAVS in a ubiquitin–proteasome manner, ultimately subverting the RLR signaling pathway ( 32 , 45 ). For GCRV, our previous studies have revealed that VP41 targets MITA, and VP56 degrades phosphorylated IRF7 ( 46 , 47 ). Our study has demonstrated that another protein of GCRV VP35 also acts on the RLR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A cystine-and histidine-rich N-terminal domain of RTA is critical for its E3 ligase activity (Yu et al, 2005). GCRV (grass carp reovirus) VP56 blocks the host IFN response and facilitates viral replication by inducing K48-linked ubiquitination and degradation of phosphorylated IRF7 upon GCRV infection (Zhang et al, 2020). In addition to NSP1, IRF9 is targeted by the immediate-early protein ORF63 encoded by VZV and simian varicella virus, which blocks JAK-STAT signaling by degrading IRF9 in a proteasome-dependent manner (Verweij et al, 2015).…”
Section: Exogenous Protein-mediated Regulation Of Irfsmentioning
confidence: 99%